INVESTIGATING TEACHERS ROLES VIEWED FROM STUDENTS- CENTERED LEARNING APPROACH IN ENGLISH LANGUAGE TEACHING - MUjahidin, Mujahidin (English Language Education Study Program, 2023)
This study examines the roles of teachers in English language instruction from a student-centered approach. It aims to investigate the instructors' roles in imparting language to students in accordance with the students-centered learning movement and to broaden their knowledge to help them become more professionals in their field. This study used library research as its primary research method, analyzing the results of the research's question using theories from many sources. Books and documents served as the research's primary sources. The findings of this study showed that the instructor must maintain a few roles during language instruction, including those of an organizer, assessor, resource, member, guide, observer, entertainer, and controller. Teachers should carry out those duties in order for the students-centered learning approach to language instruction to be successful.